Somerville ArtFarm: Transformative Placemaking and Sustainable Creativity - Lee, Madeline G. (Tufts University. Tisch Library., 2018)
￼￼￼We change places, and places change us. In a case study of the Somerville ArtFarm for Social Innovation, this idea is centered and reflected upon by design thinking, art-based analysis, and community practice. Submitted in partial fulfillment of the grant requirement of the Tufts Summer Scholars Program.